EVALUASI PROGRAM PENDIDIKAN KARAKTER BERBASIS REVOLUSI MENTAL SEKOLAH MENENGAH PERTAMA DI KABUPATEN SUMBAWA - roni hartono (Jurnal Evaluasi Pendidikan, 2020)
The purpose of this research is to; see the extent of the role of religion and the role of the environment in the character education. The research method used is an evaluation model using correlation analysis to see the relationship of the two variables, namely religion and environment. The research data was obtained from religious and environmental instruments that tested their validity using the validity of the appearance and validity of the factors with the explanatory factor analysis. The results of the study show that the overall data on environmental-based character education instruments is 3.64, which means that environment-based character education is in a good category. The results of the data analysis of all religious-based character education instruments are 3.24, which means that environment-based character education is in a good category. Correlation test results, it is known that the relationship between the two variables is positive with a correlation value of 0.221 with sig. (p count) = 0.0001 or p <0.05, which means that the relationship between the two variables is significant..